The Effect of Job Demands and Job Resources on Turnover Intention Mediated by Work Engagement at PT Prinal - Heryanto, Michael; Hendratmoko, Hendratmoko (CV. Publikasi Indonesia, 2024)
This research aims to identify the influence of job demands and job resources on turnover intention, with work engagement as a mediating variable at PT Prinal. The retail industry faces high turnover rates, posing a significant challenge at PT Prinal despite the industry's enormous potential. The study involved 250 employees of PT Prinal, using a non-probability sampling technique. Analysis was conducted with SmartPLS v4.1.0.5, utilizing Partial Least Square (PLS) and Structural Equation Model (SEM) techniques to test the hypotheses. The findings show that greater job expectations dramatically reduce employee engagement and increase the likelihood of leaving the position. The job demands at PT Prinal are generally counterproductive, as demonstrated by how they diminish employee engagement. On the other hand, more excellent job resources considerably raise employee engagement at work and lower the intention to leave. Since job demands and job resources directly affect turnover intention, work engagement plays a role in mediating the interaction between these three variables. These results highlight how crucial it is to manage job expectations and resources to boost work engagement and increase employee retention.